Diversity of Arbuscular Mycorrhizal Fungi (AMF) in Burned Forests and Peatlands in Jambi - Rike Puspitasari Tamin; Elis Kartika; Bambang Irawan; Ermadani (Postgraduate, University of Mataram, 2025)
Indonesian peat is the largest tropical peatland in the world, mostly found on the island of Sumatra. Forest and peatland fires have reduced the area of ​​forests and peatlands, necessitating rehabilitation activities considering the important role of peat in the ecosystem. Rehabilitation activities can be carried out by utilizing the presence of soil microbes in the form of Arbuscular Mycorrhizal Fungi (AMF). Fires in forests and peatlands impact the physical and chemical properties of peat soil, biodiversity, and the presence of Arbuscular Mycorrhizal Fungi (AMF). The purpose of this activity is to study the impact of forest fires on the presence of AMF in forests and peatlands using destructive methods. From this activity, it was found that the impact of peatland fires on the presence of AMF is that peatland fires will damage the natural habitat of AMF, so that the AMF population is significantly reduced; peatland conditions change, with increased soil temperature and changes in soil pH, which can affect the condition of AMF; loss of soil organic matter due to fires can reduce the availability of carbon needed by AMF for its development.